Collaborative Insight: Examining Ethical Dilemmas in Academic Integrity Among MBBS Students - Allah Bachayo Rajar, Amjad Azam, Washin Das, Partab Puri, Zameer Hussain Baladi (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: We use the sentence, "If a colleague lets me copy from their paper, I am not doing something wrong", as a phrase. The phrase "collaborative insights" implies a study of student conduct and potential problems with academic integrity, and idioms help us communicate effectively with others by conveying meaning and expressing our thoughts, ideas, and feelings. This statement reveals the problematic view towards plagiarism because it promotes unethical and lazy behaviour, undermines academic integrity, and damages the academic and professional community. Methods: A self-established questionnaire was administered to 200 MBBS college students at Muhammad Medical College Mirpurkhas. The questionnaire consisted of three categories: agree, neutral, and disagree. The collected data were analyzed using MS Excel 10, and the results were tabulated and graphed. The analysis took place at Muhammad Medical College’s central library, affiliated with Ibn-e-Sina University in Mirpur Khas, Sindh, Pakistan. Results: The crass sectional method and he survey received responses from 99, 58.2%, from the male side and 71, 41.7%, from the female side out of 170 people. 5, 3%, agree, 14, 8.2% neutral, and 151, 88.8%, disagree with the statement. Of 170 people from all academic levels, 136, 80%, disagreed with the statement 24, 14.1% responded as neutral, and 10, 5.8% agreed, showing the misunderstanding or lack of awareness about what plagiarism is and the consequences that come with it. Practical Implication Learning requires effort, practice, and dedication, and copying someone else’s work does not contribute to any of those. Copying someone else’s work without proper attribution can have legal implications, especially if the work is copyrighted. Conclusion: Of the 170 participants, 136 responded with "Disagree," indicating that the majority of the survey participants find copying from a colleague’s paper unacceptable, even if the colleague permits it. The results combine the responses to objectives providing insights into the participants’ attitude, attention, mindset, perception, approach, demeanour, and point of view towards plagiarism and their engagement in such activities. This outcome aligns with the general expectation of academic and professional integrity, which underscores the significance of honesty, originality, and ethical behaviour in all domains of work and study. Keywords: Copying, students, MMC, plagiarism, thoughts, fair-work, integrity.